Oxygen vacancy-induced strengthening and toughening in (K,Na)NbO3-based piezoceramics revealed via nanoindentation - Zhidong Zhang; Bin Yang; Longyu Chen; Zaoli Zhang; Jinming Guo (Nature Communications)
Abstract Dislocations are emerging as a pivotal factor for tailoring ceramics’ functional and mechanical properties. The introduction of point defects, notably oxygen vacancies, is unavoidable during the conventional sintering process in polycrystalline ceramics. Understanding the interplay between dislocations and oxygen vacancies is necessary for its profound implications. This work implements an innovative approach to regulate the dislocation-based incipient plasticity and creep behavior in (K0.5Na0.5)NbO3-based ceramics through oxygen vacancy engineering via CuO “hard” doping. Nanoindentation pop-in tests reveal that increasing oxygen vacancy concentrations significantly promotes the nucleation and activation of dislocations. Theoretical calculations based on density functional theory further corroborate that oxygen vacancies contribute to a decrease in Peierls stress and total misfit energy, facilitating dislocation nucleation and activation. Nanoindentation hardness and creep behavior demonstrate that oxygen vacancy impedes dislocation mobility due to solute strengthening and pinning effects. The effect of oxygen vacancies is elucidated through diverse mechanisms related to the interaction between dislocations and oxygen vacancies at different stages. This oxygen vacancy-induced strengthening and toughening strategy displays a significant potential to improve the mechanical properties of piezoelectric ceramics, while still maintaining high electrical performance.